The utility of a care model to individualize rehabilitation for critically ill patients: A scoping review - Adesulistyawati Adesulistyawati; Suhartini Ismail; Meira Erawati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Individualized care in intensive care units (ICUs) refers to holistic nursing care provided to critically ill patients, which takes into account their clinical conditions, personal life circumstances, and encourages their active involvement in the decision-making process. Purpose: To synthesize the impact of individualized care on the rehabilitation outcomes of critically ill patients. Method: A scoping review approach was employed. The literature search was conducted using PubMed, ScienceDirect, and EBSCO databases, utilizing a keyword strategy with Boolean operators